Balitsky-Kovchegov equation - Mäntysaari, Heikki (2011)
In high-energy particle physics the energy evolution of various quantities can be calculated from the Balitsky-Kovchegov (BK) equation. Depending on the frame that is used to describe the process, the BK equation can be seen to describe either the energy evolution of the virtual photon wave function or the gluon distribution function of a hadron.